Computational Blackness: The Procedural Logics of Race, Game, and Cinema, or How Spike Lee's Livin' Da Dream Productively "Broke" a Popular Video Game - Russworm, TreaAndrea M. (Black Camera, 2018)
How have video games evolved to now create meaningful stories about race and sports? This essay examines how Spike Lee's film-within-a-game, Livin' Da Dream (2015), reproduces some existing procedural and racial logics that reflect the desire to constantly manage and contain the centrality of black athletic greatness in mainstream sports and video game culture. While Lee's long-form cinematic model for turning sports video games into narrative games has been emulated across the medium as a whole, fans and gamers continually discuss the film as an evidently "broken" part of the popular NBA 2K video game series. As I argue here, however, the film-within-a-game productively insists on a default blackness when it functions as what I call "procedural cinema" (a rules and process based narrative). Ultimately, in functioning procedurally, Lee's otherwise conservative melodramatic story serves as a particularly instructive example of how computational blackness may, in systematically subverting the rules of the game, signify disruptively both within and against the machine.
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À nettoyer; _À vérifier-Cinéma